RED MUD AS BASE FOR FERROUS CEMENT SYNTHESIS - J. Mikić; M. Sudar (Journal of Engineering & Processing Management, 2010)
Consumption of red mul, of huge ballast in alumina production is nightmare for scienists who are working in the area of industrial metallurgi, one dey will become reality. Among other things of cement industry is going to help regrading assortment of products and diversity of raw material base. In this document, theoretical bases of the mentioned attempt are presented, as well as calculated indicators of charge preparation and obtaining klinker which would has and lot of good quality characters for special use. Certain difficulties, due increased content of alkali and harder sintering of this material mixture, are not insuperable.
Keywords: red mud; clay; limestone; iron cements